Effects of Nodes on the Properties of Laminated Bamboo Lumber - I. M. Sulastiningsih; Surdiding Ruhendi; Muh. Yusram Massijaya; I Wayan Darmawan; Adi Santoso (Wood Research Journal, 2013)
The objective of this study was to determine the effects of node on the properties of laminated bamboo lumber (LBL) glued with water based polymer-isocyanate adhesive. Bamboo strips for LBL fabrication were prepared from andong bamboo (Gigantochloa pseudoarundinacea) collected from private gardens in West Java. Each bamboo strip has dimension of 40 cm x 2 cm x 0.5 cm. The bamboo strips were assigned into 3 groups by the node positions: without node, with node position of 10 cm from one end of the bamboo strip, and with node position in the centre of the bamboo strip. Prior LBL fabrication, the bamboo strips were treated by cold soaking in 7% boron solution for 2 h. The laboratory scale 3-layer laminated bamboo lumbers were manufactured with 5 different layer compositions: all layers made of bamboo strips without node, inner layer made of bamboo strips with nodes at 10 cm from one end of the strip, inner layer made of bamboo strips with nodes at the centre of the strip, all layers made of bamboo strips with nodes at 10 cm from one end of the strip, and all layers made of bamboo strips with nodes at the centre of the strip.  The glue spread and cold pressing time applied were 250 g/m2 and 1 h, respectively.The results showed that the average density, moisture content, thickness swelling, bending strength and compression strength of laminated bamboo lumbers were 0.74 g/cm3, 11.3%, 2.9%, 1090 kg/cm2,and560 kg/ cm2, respectively. No delamination occurred in all samples, indicating high bonding quality. The average bonding strength (dry test) of laminated bamboo lumbers was 70.3 kg/cm2. Several properties of laminated bamboo lumber were not significantly affected by the present of nodes in the bamboo strips except the thickness swelling and compression strength.